2008
DOI: 10.1007/s00774-008-0879-8
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal metamorphosis in fibrodysplasia ossificans progressiva (FOP)

Abstract: Metamorphosis, the transformation of one normal tissue or organ system into another, is a biological process rarely studied in higher vertebrates or mammals, but exemplified pathologically by the extremely disabling autosomal dominant disorder fibrodysplasia ossificans progressiva (FOP). The recurrent single nucleotide missense mutation in the gene encoding activin receptor IA/activin-like kinase-2 (ACVR1/ALK2), a bone morphogenetic protein type I receptor that causes skeletal metamorphosis in all classically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 91 publications
(121 reference statements)
1
72
0
4
Order By: Relevance
“…Metabolic bone diseases and disorders of mineral metabolism, such as fibrodysplasia ossificans progressiva, have been suspected to cause ligament and tendon ossification. (19) In the present study, two types of ossified STSL were observed -fan-shaped and band-shaped (Table II). The fan-shaped ossified STSL, which has an osseous suprascapular foramen with a middle vertical diameter that is greater than the maximum horizontal diameter, was found to be more common (16 out of 26 scapulae).…”
Section: Discussionsupporting
confidence: 58%
“…Metabolic bone diseases and disorders of mineral metabolism, such as fibrodysplasia ossificans progressiva, have been suspected to cause ligament and tendon ossification. (19) In the present study, two types of ossified STSL were observed -fan-shaped and band-shaped (Table II). The fan-shaped ossified STSL, which has an osseous suprascapular foramen with a middle vertical diameter that is greater than the maximum horizontal diameter, was found to be more common (16 out of 26 scapulae).…”
Section: Discussionsupporting
confidence: 58%
“…(1) Several conditions may lead to soft tissue ossification, and these include fibrodysplasia ossificans progressiva and traumatic myositis ossificans. The first is a rare congenital disorder with a frequency of 1 per 2 million (2) that is caused by a recently discovered recurrent missense mutation in the BMP type 1 receptor activin receptor 1A/activin-like kinase-2 (ACVR1/ALK2). (3) Sporadic mutations and an autosomal dominant pattern of inheritance are responsible for the disease, in which ossification can occur with or without injury and typically grows in a predictable pattern.…”
Section: Introductionmentioning
confidence: 99%
“…(8,9) A few years later, Chalmers and colleagues proposed that three essential conditions were required to induce HO: (1) osteogenic precursor cells, (2) inducing agents, and (3) a permissive environment. (10) Among the growth factors with osteoinductive potential, the most important are bone morphogenetic proteins (BMPs), which belong to the transforming growth factor b (TGF-b) superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…Констатация сочетания фиброза и кальцифика ции, понятная лишь с позиций гистогенетической общности мезенхимальных предшественников со единительной и костной тканей, изменилась в конце 1990 х годов при выявлении биохимических и моле кулярных звеньев патогенеза фиброзирующих и ос сифицирующих заболеваний в целом [29][30][31], в т. ч. и системы органов дыхания [11,[32][33][34], а также таких клинически значимых заболеваний, как ге теротопическая оссификация у обездвиженных па циентов с ожогами, обширными травмами скелета, черепно мозговыми или спинальными травма ми [35][36][37] и прогрессирующая оссифицирущая фибродисплазия [38][39][40]. С этого времени в патоге нетический каскад стали включаться про и проти вовоспалительные, ростовые факторы и рецепторы к ним, молекулы адгезии, сигнальной трансдукции, регуляторы трансляции (активирующие и ингибиру ющие).…”
Section: заметки из практикиunclassified